Meningkatkan hasil belajar pembagian dengan menggunakan kartu kelipatan berwarna - Naswan Naswan (Universitas Hamzanwadi, 2022)
The use of teaching methods as well as the selection and use of teaching aids in learning mathematics can create a quality learning process and optimal results for students. This study aims to examine the use of “Colored multiples card (Ketupat Warna)” in increasing students' understanding of mathematical division operations in elementary school students. This type of research is classroom action research (CAR) with data collection using test and observation instruments. Based on the results of data analysis that has been carried out, it can be concluded that 97.5% of students experienced an increase in learning evaluation results. This can be proven through evaluation with student scores in the first cycle only 24 students or (58.5%) getting a score of 60, and increasing in the second cycle to 40 students or (97.5%) getting a score of 60 Thus the use of the props